Modeling the F region ionosphere peak height variations over Malaysia by Antenna Pattern Synthesis Technique - Zeti Akma, Rhazali (2014)
The ionospheric F region over Malaysia is still an issue to many radio communication enthusiasts. The actual height of this layer is not well defined. Models available are mostly reliable for temperate zones. This thesis describes the determination of the actual F layer height and proposed a unique model to represent the height variations. The ionospheric F region is observed via ionograms, produced by the ionosonde operated at Parit Raja (2oN, 103oW, dip 14.3o), Batu Pahat, Malaysia. The ionogram gives the virtual height representation of the ionosphere. POLAN ionogram inversion program is used to determine the real height of the ionospheric layer. The observations are held during period of moderate to low solar activity of solar cycle 23 (2005 to 2010). However, in this work, only hourly data of March, June, September, and December, 2006 and 2007, are examined. The data are statistically analysed to summarize their main characteristics. The actual height of the F layer is determined from the median values and the coefficient of variability quantifies the height deviations. To derive the mathematical representation of the variations, the least-squares regression technique is used to fit functions to the median data. The best fit function is the descriptive model that describes the variations. A new model of ionospheric height variations is also proposed on the same basis. The ionospheric height time variation which is a cyclic event is re-represented in polar coordinate form. The cyclic representation which approximates an antenna radiation pattern allows the development of antenna equivalent model of peak height variations. The association of ionospheric height variations to the radiation pattern of antenna array is the novelty idea of this study. The observation results indicate that the median height of peak electron density, hmax, varies from 420km in June to 550 km in other months during noon time. The night-time average heights rest around 300 km for all months. The daytime peak is found highest in December solstice season and lowest in June season while post sunset peaks are not seen during this period. The descriptive mathematical model of diurnal variations shows that the variations fit well into a four-term Fourier series model. The two-element arrays with array spacing in the x-direction of λ/8, and phase of π/3, and with element spacing in the y-direction of λ/4, and phase of zero, is the optimal array configuration which signifies the variations. The results show that an array of two-element arrays antenna is suitable to represent the ionosphere peak height variations over Malaysia during moderate to low solar activity period.